2001
DOI: 10.1007/s00464-001-9033-6
|View full text |Cite
|
Sign up to set email alerts
|

An experimental model of gastroschisis using fetoendoscopy

Abstract: Our experience shows that this experimental model of gastroschisis is feasible and reproducible, and that a repeated amnioinfusion can be performed with an in-dwelling catheter in pregnant ewes. The use of an implantable port is safer than a simple exteriorized catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A fetal sheep model of gastroschisis which was created by a hybrid approach (maternal laparotomy, manipulation of the uterus, and transuterine fetoscopy) was treated with amnioinfusion by an implantable port implanted during creation of the gastroschisis: a total of 46.7% of the fetuses survived the procedure, an amniotic infection occurred in 34.6% of cases. It could be demonstrated that continuous amnioinfusion appears technically feasible by implanted port devices [61].…”
Section: Animal Interventionsmentioning
confidence: 99%
“…A fetal sheep model of gastroschisis which was created by a hybrid approach (maternal laparotomy, manipulation of the uterus, and transuterine fetoscopy) was treated with amnioinfusion by an implantable port implanted during creation of the gastroschisis: a total of 46.7% of the fetuses survived the procedure, an amniotic infection occurred in 34.6% of cases. It could be demonstrated that continuous amnioinfusion appears technically feasible by implanted port devices [61].…”
Section: Animal Interventionsmentioning
confidence: 99%
“…In their recent article describing a fetoendoscopic sheep model of gastroschisis, Guys et al [10] cited our experience with amniotic fluid exchange under the term ''amnioinfusion.'' However, the procedure of amniotic fluid exchange differs from amnioinfusion.…”
mentioning
confidence: 99%